2023
DOI: 10.1111/jdi.14054
|View full text |Cite
|
Sign up to set email alerts
|

Changes in glycemic control and skeletal muscle mass indices after dapagliflozin treatment in individuals with type 1 diabetes mellitus

Abstract: Aims/IntroductionDapagliflozin is used for individuals with type 1 diabetes, although the effect of this medication on skeletal muscle mass is not well established. In addition, there are few studies examining the effects of good glycemic control on skeletal muscle mass in type 1 diabetes patients. We investigated changes in glycemic control and skeletal muscle mass with dapagliflozin in individuals with type 1 diabetes, and the association between these changes.Materials and MethodsThis was a post‐hoc analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…The acceleration of population aging had led to an increased prevalence of DS, characterized by elevated rates of falls, functional disability, and fractures. More research spanning from basic science to clinical studies, has revealed the complexity of DS, however, no specific treatments have been established. Therefore, it is crucial to identify new targets for sarcopenia, muscle mass, and function loss caused by sustained hyperglycemia. In our present study, we comprehensively investigated the interactions of gut–muscle axis by evaluating multiomics, including gut microbiome, gastrocnemius metabolome, and proteome.…”
Section: Discussionmentioning
confidence: 99%
“…The acceleration of population aging had led to an increased prevalence of DS, characterized by elevated rates of falls, functional disability, and fractures. More research spanning from basic science to clinical studies, has revealed the complexity of DS, however, no specific treatments have been established. Therefore, it is crucial to identify new targets for sarcopenia, muscle mass, and function loss caused by sustained hyperglycemia. In our present study, we comprehensively investigated the interactions of gut–muscle axis by evaluating multiomics, including gut microbiome, gastrocnemius metabolome, and proteome.…”
Section: Discussionmentioning
confidence: 99%